Research Status and Progress of Third-generation EGFR-TKIs in Elderly Patients with Non-small Cell Lung Cancer - Xue CHEN; Yijia SUN; Lihong ZHANG; Bo JIANG (Chinese Journal of Lung Cancer)
For patients with advanced non-small cell lung cancer (NSCLC) harboring sensitive epidermal growth factor receptor (EGFR) mutations, guidelines prioritize the use of third-generation EGFR-tyrosine kinase inhibitors (EGFR-TKIs), which offer higher objective response rate (ORR), longer progression-free survival (PFS), and better quality of life. However, due to the low proportion of elderly patients enrolled in clinical trials, the existing evidence is insufficient to fully guide clinical practice. This review examines the efficacy and safety differences of third-generation EGFR-TKIs as monotherapy or in combination in the elderly NSCLC by integrating subgroup analyses or pre-specified research objectives from prospective and retrospective studies. The results show that third-generation EGFR-TKIs have comparable efficacy in elderly patients to younger populations and are well-tolerated. Although combination therapies may extend survival time, the associated increased toxicity necessitates careful risk-benefit assessment.